2019
DOI: 10.1016/j.apsoil.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of soil functions to transient and persistent stresses is improved more by residue incorporation than the activity of earthworms

Abstract: Resilience of soil functions to transient and persistent stresses is improved more by residue incorporation than the activity of earthworms. Applied Soil Ecology, 139. pp. 10-14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Our study demonstrated greater resilience of C and N processes to heat than to Cu (Figure 2), which is attributed to our heat application being a more transient stress with short and acute effect (Shu et al, 2019). Although soil pH has no direct impact on heat, the effect of pH on functional and microbial resilience to heat may mostly be attributed to selective effects of soil pH on microbial taxa.…”
Section: The Effects Of Soil Ph On the Resistance And Resilience Of F...mentioning
confidence: 60%
See 2 more Smart Citations
“…Our study demonstrated greater resilience of C and N processes to heat than to Cu (Figure 2), which is attributed to our heat application being a more transient stress with short and acute effect (Shu et al, 2019). Although soil pH has no direct impact on heat, the effect of pH on functional and microbial resilience to heat may mostly be attributed to selective effects of soil pH on microbial taxa.…”
Section: The Effects Of Soil Ph On the Resistance And Resilience Of F...mentioning
confidence: 60%
“…Resistance was the stability measured at 1 day, while resilience was the stability after 1 to 56 days following stress (Shu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance was defined as stability measured at day 1 after perturbation, while resilience was estimated as the integrative stability after day 1 up to 28 days following stress [27].…”
Section: Discussionmentioning
confidence: 99%
“…Soil C mineralization was measured as the short-term cysteine was prepared and filter-sterilised [27]. Two g soil was mixed with 120 µl of this solution to give a concentration of 3 mg C soil g -1 and stored in an air-tight gas vial (22 ml) over 24 hours at 20 °C, prior to measurement of CO2-C concentration on a gas chromatograph (Agilent 7890A, UK) with a thermal conductivity detector (Agilent Technologies, UK).…”
Section: Soil C Mineralizationmentioning
confidence: 99%